House banks in out-of-court reorganization: Evidence from Austria - Stefan Mayr; Christine Duller; Kerstin Stumbauer (The Journal of Entrepreneurial Finance (JEF), 2020)
The main purpose of this article is to study the role of house banks in out-of-court reorganization. Banks are traditionally one of the most important financial resources for firms. Especially in financially difficult times like those we now face due to the coronavirus, it can make a difference whether a bank supports its clients and accompanies firms through a crisis or not. With the help of relationship lending theory, we review the existing literature on this topic. Next, based on empirical findings from Austrian banks, we derive implications for corporate practice. The empirical study covers a sample of 658 firm reorganizations in Austria. The data were collected anonymously by different banks processing the cases in their workout departments between January 2011 and December 2013. Correlation analysis and logistic regression were applied to analyze the data. The findings indicate that house banks, despite their relationship of trust, must be critical in their assessment of reorganization projects due to the danger of zombie lending. The four most important prerequisites for completing an out-of-court reorganization were a new loan, an open and proactive communication policy on the part of the distressed company, management changes, and a financial contribution from existing shareholders. The findings show that bank-supported out-of-court reorganization has a high probability of success. A recommendation to entrepreneurs is to respond rapidly to financial distress and maintain open communication with stakeholders, in particular banks. The findings indicate that the implementation of Directive (EU) 2019/1023 on preventive restructuring frameworks in the European Union is crucial to enable bank-led reorganizations.
Keywords: G21; G34; 650; Reorganization; House bank; Out-of-court; Workout; Relationship lending